Tikopia OT11 (eHRAF World Cultures, 1995)
Tikopia is a small volcanic island that is part of the Solomon Islands. This file of 28 documents contains data on the indigenous inhabitants of Tikopia and Cherry Island, in the Santa Cruz Group